2010
DOI: 10.1038/ijo.2010.87
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the triple monoamine reuptake inhibitor tesofensine on energy metabolism and appetite in overweight and moderately obese men

Abstract: Background: Tesofensine (TE) is a new drug producing twice the weight loss in obese individuals as seen with currently marketed drugs. It inhibits the presynaptic reuptake of the neurotransmitters noradrenaline, dopamine and serotonin, and is thought to enhance the neurotransmission of all three monoamines. The mechanisms by which it produces weight loss in humans are unresolved. Objective: The aim of this study is to investigate the mechanism(s) behind weight reduction by measuring energy expenditure and appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 32 publications
2
33
0
2
Order By: Relevance
“…Increases in heart rate and blood pressure were also observed, which may limit further increases in dosing. In another phase II trial with overweight and moderately obese individuals, 2.0 mg of tesofensine was given daily for 7 days and 1.0 mg given daily for another 7 days [44]. The treatment group showed a 1.8 kg weight loss above placebo, higher satiety ratings and lower food intake.…”
Section: Obesity Drugs Under Developmentmentioning
confidence: 99%
“…Increases in heart rate and blood pressure were also observed, which may limit further increases in dosing. In another phase II trial with overweight and moderately obese individuals, 2.0 mg of tesofensine was given daily for 7 days and 1.0 mg given daily for another 7 days [44]. The treatment group showed a 1.8 kg weight loss above placebo, higher satiety ratings and lower food intake.…”
Section: Obesity Drugs Under Developmentmentioning
confidence: 99%
“…Increases in heart rate and blood pressure were also observed, which may limit further increases in dosing. In another phase II trial with overweight and moderately obese individuals, 2.0 mg of tesofensine was given daily for 7 days and 1.0 mg given daily for another 7 days (Sjodin et al, 2010). The treatment group showed a 1.8 kg weight loss above placebo, higher satiety ratings and lower food intake.…”
Section: Obesity Therapies Under Developmentmentioning
confidence: 99%
“…126 Tesofensine increases satiety and may increase energy expenditure. 127128 No pediatric studies have been reported.…”
Section: Current Pharmacotherapeutic Options For Obesity Treatmentmentioning
confidence: 99%